Perancangan Sistem Smart Egg Incubator sebagai Optimalisasi Pemanfaatan Energi Terbarukan di Ngalau Baribuik, Padang - Refdinal Nazir; Andi Pawawoi; Melda Latif; Muhammad Imran Hamid; Pinto Anugrah; Eka Fitrianto (Warta Pengabdian Andalas, 2023)
Micro Hydro (PLTMH) Ngalau Baribuik, Padang - West Sumatra, has operated since 2012. It is currently the only source of electricity for the local community, some of whom work as chicken breeders. Based on community service activities in 2021, information was obtained that the PLTMH's electricity had yet to be utilized optimally. Meanwhile, chicken breeders also needed egg incubators to increase their productivity. This community service activity aims to design an IoT-based automatic egg incubator to optimize the use of renewable energy. Activities started with field visits, making initial plans, designing and testing the machine, handing over the machine, and disseminating knowledge. The designed a smart egg incubator worked well after a 21-day hatching test for chicken eggs. The IoT technology installed on the device also functions appropriately and can show real-time temperature and humidity on mobile devices.